1996
DOI: 10.1038/381387a0
|View full text |Cite|
|
Sign up to set email alerts
|

Two distinct mechanisms for long-range patterning by Decapentaplegic in the Drosophila wing

Abstract: Secreted signalling molecules provide cells with positional information that organizes long-range pattern during the development of multicellular animals. Evidence is presented that localized expression of Decapentaplegic instructs cells about their position along the anterior-posterior axis of the Drosophila wing in two distinct ways. One mechanism is based on the local concentration of the secreted protein; the other is based on the ability of the cells to retain an instruction received at an earlier time wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
434
3
5

Year Published

1996
1996
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 607 publications
(451 citation statements)
references
References 41 publications
9
434
3
5
Order By: Relevance
“…Second, activin and TGF-␤1 are able to signal across layers of cells lacking receptors (Gurdon et al, 1994), indicating that these factors were not inducers of other morphogens and, therefore, were acting directly on cells at some distance from their source. Elegant genetic studies using receptorless cells had previously led to similar conclusions for Dpp (BMP4) and Wingless (Wnt) signaling in Drosophila (Nellen et al, 1996;Zecca et al, 1996;Lecuit et al, 1996). A weakness of the Xenopus studies is that they relied on the use of ligands and receptors (activin and TGF-␤1 and a TGF-␤ receptor) that are not expressed in the embryo.…”
Section: Establishment Of Morphogen Gradients Part I: Evidence For Dmentioning
confidence: 99%
“…Second, activin and TGF-␤1 are able to signal across layers of cells lacking receptors (Gurdon et al, 1994), indicating that these factors were not inducers of other morphogens and, therefore, were acting directly on cells at some distance from their source. Elegant genetic studies using receptorless cells had previously led to similar conclusions for Dpp (BMP4) and Wingless (Wnt) signaling in Drosophila (Nellen et al, 1996;Zecca et al, 1996;Lecuit et al, 1996). A weakness of the Xenopus studies is that they relied on the use of ligands and receptors (activin and TGF-␤1 and a TGF-␤ receptor) that are not expressed in the embryo.…”
Section: Establishment Of Morphogen Gradients Part I: Evidence For Dmentioning
confidence: 99%
“…Both Spalt (Lecuit et al 1996;Nellen et al 1996) and the PRDII-BF1 family member Schnurri (Arora et al 1995;Grieder et al 1995) have been shown to be targets of signaling by the TGF-f3-1ike protein Decapentaplegic. The sequence similarities among SEM-4, Spalt, and PRDII-BF1 family members raise the possibility that SEM-4 activity might also be controlled by a signal transduction pathway.…”
Section: V5paapp Cell Death Pnp Hypodermal Cellsmentioning
confidence: 99%
“…Dpp acts as a long-range morphogen and regulates gene expression in imaginal discs in a concentration-dependent manner (Lecuit et al, 1996;Nellen et al, 1996). In response to Dpp signaling, an activated form of the Smad transcription factor, Mothers against dpp (Mad), is generated.…”
Section: Introductionmentioning
confidence: 99%